Influência de estruturas geológicas bidimensionais no campo geoeletromagnético na presença do eletrojato equatorial - SILVA, Marcos Welby Correa (Universidade Federal do Pará, 2014)
The Earth acts as a large magnet, whose field resembles one that is generated by a magnetic dipole. This field presents intensity changes that vary with observation location and the local time. The main part of the geomagnetic field is created within the Earth by electromagnetic processes. Extensive studies showed that there are also contributions from outside the Earth, mainly from solar origin. Among these outside sources there are anomalies of the magnetic field that arise from an diurnal increase of the electric current in a narrow strip located in the ionosphere, with east-west direction, centered above the magnetic equator and denominated Equatorial Electrojet (EEJ). Occasionally these currents present flow reversions, therefore denominated Counter-Electrojet (CEJ). Several authors have been studying the effects of the EEJ on the geomagnetic observations. They are interested in the combined effect of the equatorial electrojet and the 1-D e 2-D conductive geological structure underneath. In these works the 2-D structure is always considered parallel to the electrojet, which is a quite restrictive hypotheses in view to realistic geological situation, in that two-dimensional structures can have any direction in relation to the electrojet. We present in this work the solution of this problem without this restriction. Thus, here we present the geomagnetic fields due to a two-dimensional structure that possess oblique strike in relation to Equatorial Electrojet, through profiles of the electric and magnetic fields, calculated on the surface and forming arbitrary direction to the 2-D conductive heterogeneity. Further, we also evaluate the influence of an arbitrarily oriented two-dimensional structure would cause on the Magnetotelluric data, under the quatorial Electrojet. In the development of this work, we applied the method of finite elements with the EEJ and CEJ as electromagnetic source, that was represented by a sum of gaussians distributions of current density. This source was decomposed in the parallel and the perpendicular directions to the 2-D structure, resulting in the mode TE1 and the coupled mode TE2 and TM, respectively. We solved the coupled mode applying a Fourier Transform in the Maxwell equations and one Inverse Fourier Transform in the transformed-domain solution. According to the numerical experiments on a interpretative model of Parnaíba Basin Conductivity Anomaly, formed by a large 3000 ohm-m body inside a very conductive (1ohm-m) external structure, we conclude that the presence of the CEJ causes an inversion in the anomaly. We also conclude that at high frequencies the components of the electric field present smaller influence of the internal part of the 2-D body than the external part. Otherwise, we observed this behavior in the magnetic field at low frequencies. Varying the frequencies, we saw the effects of the “skin-depth” mainly in the magnetic field. Besides, there are situations where electric field is insensitive to the internal structure of the model for all values of the frequency used. With regard to the angle θh between the strike of the conductive heterogeneity and the EEJ direction, we observe the TM mode naturally when θh is different from 0°. In this case, the TE mode is composed of two components, one decomposition of the EEJ parallel to the heterogeneity and the other perpendicular to it. As consequence, the E and B fields have all their three components. When we analyzed the influence of the angle between the direction of the profile of fields and the strike of the 2-D heterogeneity, we conclude that its variation causes an asymmetry on the anomalies, which give an idea about the profile’s direction. Finally, we conclude that one of the influences that the distance between the center of the electrojet and center of the 2-D structure causes on the fields is related to the reverse currents, because at 500 km from the EEJ’s center, these currents have their maximum intensity. In the MT soundings, we also used the EEJ and CEJ as primary source and we compared our results with the plane wave response. We noted that the components of the geomagnetic field, used to evaluate the impedance, have an influence from the coupling factor between the TE2 and TM modes. Moreover, this influence become greater with decreasing of the frequency and for resistive host. However, the coupling factor do not affects the MT response at frequencies higher than 10-2 Hz. For lower frequencies, about 10-4 Hz, we detect two kinds of pertubations on the MT data with respect to the plane-wave one: the first is due the presence of the 2-D electromagnetic source (EEJ and CEJ) as primary field, which violates the plane wave hypothesis; and the second is caused by the coupled TE and TM modes because additional electric currents arise in the heterogeneity’s direction when it is oblique to EEJ. These efects increase with the resistivity of the environment. In conclusion, the strike of a large conductive 2-D structure relative to the direction of the EEJ or CEJ do have influence on the geomagnetic field. On the other hand, for shallow magnetotelluric studies (frequencies higher than 10-3 Hz) the effect of angle between the strike of the 2-D geological structure and the direction of the EEJ is not so important. However, for litospheric studies (frequencies lower than 10-3 Hz) the coupling between the two modes can not be ignored.